2010
DOI: 10.11646/zootaxa.2344.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochus farsicus sp.n. from Iran and notes on other Palearctic species of the genus (Coleoptera: Hydrophiloidea: Hydrochidae)

Abstract: The family Hydrochidae (or subfamily Hydrochinae for some authors) includes one recognised genus (Hydrochus Leach) with more than 200 species and a worldwide distribution (Hansen, 1999; Short & Hebauer, 2006). The West Mediterranean is among the most diverse areas for the genus in the Palearctic Region, with 12 species known from Spain and Morocco, including several endemic species described recently (Hansen, 2004). On the contrary, in the East Mediterranean and the Middle East few species are known so far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…After Hydrochus farsicus was identified as a new species by Hidalgo-Galiana et al (2010) from Iran, we rechecked the samples and found out that they most closely resembled the Hydrochus farsicus (especially the aedaegus). An illustration of the aedeagus of Turkish H. farsicus is shown for further comparison (Figure 1).…”
Section: Notesmentioning
confidence: 99%
“…After Hydrochus farsicus was identified as a new species by Hidalgo-Galiana et al (2010) from Iran, we rechecked the samples and found out that they most closely resembled the Hydrochus farsicus (especially the aedaegus). An illustration of the aedeagus of Turkish H. farsicus is shown for further comparison (Figure 1).…”
Section: Notesmentioning
confidence: 99%